Does training with 3D videos improve decision-making in team invasion sports?. Issue 8 (17th April 2016) - Hohmann, Tanja; Obelöer, Hilke; Schlapkohl, Nele; Raab, Markus
Abstract: We examined the effectiveness of video-based decision training in national youth handball teams. Extending previous research, we tested in Study 1 whether a three-dimensional (3D) video training group would outperform a two-dimensional (2D) group. In Study 2, a 3D training group was compared to a control group and a group trained with a traditional tactic board. In both studies, training duration was 6 weeks. Performance was measured in a pre- to post-retention design. The tests consisted of a decision-making task measuring quality of decisions (first and best option) and decision time (time for first and best option). The results of Study 1 showed learning effects and revealed that the 3D video group made faster first-option choices than the 2D group, but differences in the quality of options were not pronounced. The results of Study 2 revealed learning effects for both training groups compared to the control group, and faster choices in the 3D group compared to both other groups. Together, the results show that 3D video training is the most useful tool for improving choices in handball, but only in reference to decision time and not decision quality. We discuss the usefulness of a 3D video tool for training of decision-making skills outside the laboratory or gym.